Optimal Timing for Corticosteroid Therapy in Idiopathic Granulomatous Mastitis: A Retrospective Analysis Highlighting Early Intervention Efficacy - Wang P; Sun JZ; Fang HY; Yang DJ; Ren GS (Dove Medical Press, 2024)
Pin Wang,1- 4 Jia-Zheng Sun,3,4 Hui-Ying Fang,3,4 De-Juan Yang,3,4 Guo-Sheng Ren3,4 1Department of General Surgery, the Third People's Hospital of Chengdu, Chengdu, People's Republic of China; 2Center of Breast and Thyroid Surgery, the Third People's Hospital of Chengdu, Chengdu, People's Republic of China; 3Chongqing Key Laboratory of Molecular Oncology and Epigenetics, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 4Department of Breast and Thyroid Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Pin Wang, Email wangpin109@126.comBackground: Idiopathic granulomatous mastitis (IGM) is a chronic breast condition known for its aggressive nature and tendency for persistence and recurrence. Steroids are commonly used as the first-line treatment for IGM, but issues such as the optimal timing, and duration of treatment remain debated.Methods: We retrospectively analyzed 343 IGM cases treated at the Third People's Hospital of Chengdu from September 2012 to September 2023. Based on inclusion and exclusion criteria, a total of 188 patients were included in the study. Patients were categorized into lump (78 cases), abscess (81 cases), and sinus tract stages (29 cases) according to their initial diagnosis upon admission. Prednisolone was initiated at 0.75 mg/kg/day, and after effective treatment, the dosage was adjusted by 5- 10 mg weekly, followed by a maintenance dose of 2.5- 5 mg/day. Clinical characteristics, treatment responses, adverse effects, recurrence rates, and follow-up data were assessed.Results: The median duration of prednisone treatment in our study was 87 days (range, 21- 281 days). Positive response rates to prednisolone were 78.2% in the lump stage, 60.5% in the abscess stage, and 62.1% in the sinus tract stage. Continuing low-dose prednisone for 3 months post-effective treatment reduced recurrence rates and side effect risks. Weight gain was the most common side effect (39.36%).Conclusion: Early steroid therapy, especially in the lump stage, demonstrated superior efficacy. Following a regimen of starting with a full dose, tapering slowly, and maintaining a low dose for around 3 months steroids treatment is recommended to minimize recurrence rate and adverse effects.Keywords: Idiopathic Granulomatous Mastitis (IGM), Steroids, Breast, Prednisolone